2006
DOI: 10.1016/j.febslet.2006.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal interplay among commensal and pathogenic bacteria: Lessons from flagellin and Toll‐like receptor 5

Abstract: Toll‐like receptors (TLR) detect pathogen‐associated molecular patterns (PAMP) and play a crucial role in triggering immunity. Due to their large surfaces in direct contact with the environment, mucosal tissues are the major sites of PAMP‐TLR signalling. How innate and adaptive immunity are triggered through flagellin–TLR5 interaction is the main focus of the review. In view of recent reports on genetic polymorphism, we will summarize the impact of TLR5 on the susceptibility to mucosal infections and on variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
54
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 90 publications
0
54
0
2
Order By: Relevance
“…TLR5 has been identified as the main pattern recognition receptor required for flagellinmediated immune signalling [17]. TLR5 signalling depends on MyD88 and results in activation of MAPK, nuclear translocation of NF-kB and production of various pro-inflammatory cytokines and chemokines [18]. Moreover, a previous report found that TLR5 cooperates with TLR4, suggesting that TLR4 deficiency will affect flagellin-mediated responses [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR5 has been identified as the main pattern recognition receptor required for flagellinmediated immune signalling [17]. TLR5 signalling depends on MyD88 and results in activation of MAPK, nuclear translocation of NF-kB and production of various pro-inflammatory cytokines and chemokines [18]. Moreover, a previous report found that TLR5 cooperates with TLR4, suggesting that TLR4 deficiency will affect flagellin-mediated responses [19].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in the respiratory tract, bronchial and alveolar epithelial cells with alveolar macrophages are the main sentinels in the detection of microbial signals through innate receptors like the TLRs [33]. A variety of studies have demonstrated that lung and intestinal epithelial cells respond to flagellin by producing PMN-specific chemokines (CXCL1, CXCL5 or CXCL8), cytokines (TNF-a and IL-6) and antimicrobial molecules (NO and h-bD2) [18]. These findings agree with TLR5's predominant expression in lung and intestinal epithelial cells; hence, the epithelium is considered to be one of the main TLR5-responsive compartments [34,35].…”
mentioning
confidence: 99%
“…However, TLRs detect specific molecules which are not exclusive to pathogenic organisms. For example, TLR4 recognizes LPS [37], which is present on all Gram-negative bacteria, including non-pathogenic bacteria, and TLR5 [42] recognizes flagellin [43], also expressed by most gut commensal [44]. Various TLR ligands have been shown to modulate the immune response [45][46][47] and act as vaccine adjuvants regardless of their pathogenic or non-pathogenic origin (i.e LPS, CpG DNA).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that i.v. injection of flagellins promotes a systemic response, characterized by the production of proinflammatory mediators (such as TNF-␣ or IL-6) and DC activation (5,6,(13)(14)(15)(16)(17). Furthermore, flagellins trigger mucosa-specific innate and adaptive defense mechanisms (18 -20).…”
Section: Deletion Of Flagellin's Hypervariable Region Abrogates Antibmentioning
confidence: 99%
“…Bacterial flagellins (the major flagella components in many bacterial pathogens) are specific, unique agonists for TLR5 activation (5,6). The FliC flagellin from Salmonella enterica serovar Typhimurium is the paradigm for studies on flagellum structure-function, immunity, and TLR5 signaling (6 -9).…”
Section: Deletion Of Flagellin's Hypervariable Region Abrogates Antibmentioning
confidence: 99%